Tourism and Security in Nepal - Chhetri, Rup Kumar (Journal of Tourism & Adventure, 2018)
This paper discusses the concept of tourism and security in Nepal and focuses on the association in between tourism and security aspects. Tourism is important for leisure, business, education, culture and recreation. Tourism industry is a fast developing sector for the economy worldwide and becoming a popular global leisure activity. As a fast growing industry in the today’s world, tourism industry events are getting more attraction for study and appropriate intervention. The key question this paper raises is whether there is association between tourism and security in Nepal. It answers rationally to its prime research questions like; what are the dimensions of tourism and security in Nepal? What is the association in between tourism and security in Nepal? In order to look for the answers of these questions, Thamel area was chosen for study site as it is popular among people and the major tourism hub in Nepal. The findings of the study show varied association in between tourism sector and tourism security sector on the specifics such as tourism, hospitality, events and security in Nepal. Although tourism enterprises increasingly realize the aspects of tourism, hospitality, events management and relevant security parameters, but the extent to which they are strategically used varies. The assessment revealed the impacts of tourism on security aspects and vice versa. So, the impacts of security situation on tourism sector have a certain and intermingled association. Even the findings aligned with above said statement which reflects the limitations and gap in between the tourism sector and tourism security sector in term of setups, coordination and execution. That is why, it roves and looking for the rational, empirical and cognitive improvement and development on those identified aspects which are keenly observed during the research process.